2021
DOI: 10.1007/s40820-021-00592-9
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Ultrathin Flexible Thermoplastic Polyurethane/Carbon Black Fibrous Film Strain Sensor with Adjustable Scaffold Networks

Abstract: In recently years, high-performance wearable strain sensors have attracted great attention in academic and industrial. Herein, a conductive polymer composite of electrospun thermoplastic polyurethane (TPU) fibrous film matrix-embedded carbon black (CB) particles with adjustable scaffold network was fabricated for high-sensitive strain sensor. This work indicated the influence of stereoscopic scaffold network structure built under various rotating speeds of collection device in electrospinning process on the el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
179
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 248 publications
(180 citation statements)
references
References 55 publications
0
179
1
Order By: Relevance
“…(D) Sensing application of the strain sensor when monitoring speaking different words with sample fixing at neck. Reproduced with the permission from [188], copyright the Springer Nature, 2021. (E) Control of avatar fingers in the virtual environment using wireless smart glove system.…”
Section: Figure 6 (A-c)mentioning
confidence: 99%
“…(D) Sensing application of the strain sensor when monitoring speaking different words with sample fixing at neck. Reproduced with the permission from [188], copyright the Springer Nature, 2021. (E) Control of avatar fingers in the virtual environment using wireless smart glove system.…”
Section: Figure 6 (A-c)mentioning
confidence: 99%
“…In general, the current EHFs collect various forms of energy by introducing fillers with different properties including carbon nanotubes, metal nanowires and conducting polymer to the elastic matrix [11][12][13][14][15][16][17]. Nevertheless, the nanofillers are easy to agglomerate during the preparation process and limit the application in practice [18,19]. Therefore, it is extremely important to select fillers with good dispersion and excellent performance.…”
Section: Introductionmentioning
confidence: 99%
“…Conductive polymer composites (CPCs) with low density, stable chemistry, easy molding and flexible design, are one of the main candidates for replacing metals. [10][11][12] Research has shown that carbon-based materials, such as carbon nanotubes (CNT), carbon fibers (CF) and graphene, are effective conductive fillers for EMI shielding composites. [13-,16] As we all know, EMI shielding mainly includes two aspects: absorption and reflection.…”
Section: Introductionmentioning
confidence: 99%